Pengaruh Sumber Daya Manusia dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah pada Badan Pendapatan, Pengelolaan Keuangan dan Aset Daerah (BPPKAD) Kabupaten Sukoharjo - Rafieq, Muhammad; Azhari (PENG: Jurnal Ekonomi dan Manajemen, 2024)
This research is to see the influence of Human Resources and Internal Control Systems on the Quality of Regional Government Financial Reports at the Sukoharjo Regency Regional Revenue, Financial and Asset Management Agency (BPPKAD). The population and sample in this study were all BPPKAD Sukoharjo Regency employees. This research uses multiple linear regression analysis with primary data obtained using a data collection method using a questionnaire. The research results showed that human resources have an influence on the quality of local government financial reports, so that as human resource competency increases, the quality of local government financial reports will increase. And the internal control system also influences the quality of local government financial reports, this shows that the more the internal control system improves, the quality of local government financial reports will increase.